1974
DOI: 10.1159/000197528
|View full text |Cite
|
Sign up to set email alerts
|

Studies with Two Gastrin Antisera of Different Specificity for Gastrins I and II

Abstract: Two gastrin antisera with different specificity for gastrins I and II have been compared by radioimmunoassay. Although both were produced in rabbits in response to repeated injections of synthetic human gastrin I (SHG I), one (AS 4) binds well with SHG I and porcine gastrin I (PG I), yet shows little cross-reactivity with porcine gastrin II (PG II), whilst the other (AS 35) shows equal binding with porcine gastrins I and II and SHG I. Fasting serum gastrin levels in normals, patients with duodenal ulcer, gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1975
1975
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 11 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Such behaviour of gastrin antisera perhaps makes it unlikely that an antibody will be raised against one of the molecular species of gastrin, to which it is totally specific. Nevertheless, antisera relatively more specific than those described in this study have been reported (Hansky, Soveny and Korman, 1974).…”
Section: Discussionmentioning
confidence: 48%
“…Such behaviour of gastrin antisera perhaps makes it unlikely that an antibody will be raised against one of the molecular species of gastrin, to which it is totally specific. Nevertheless, antisera relatively more specific than those described in this study have been reported (Hansky, Soveny and Korman, 1974).…”
Section: Discussionmentioning
confidence: 48%
“…However, an amino-terminal fragment of G17 has been found in the serum of patients with ZES , so that measurements made with such antisera cannot be attributed to immunoreactive G17 alone. Hansky et al (1974) found significant differences between duodenal ulcer and normal subjects in fasting serum gastrin measured with two antisera-one of which cross-reacted with the unsulphated form of G17 but not the sulphated form, and the other cross-reacted equally with sulphated and unsulphated G17. The G17 specific antiserum (L6) used in the present study does not cross-react with G34 or with carboxyl-and amino-terminal fragments of G17 and shows almost equal immunoreactivity with sulphated and unsulphated G17 (Dockray and Taylor, 1976).…”
Section: Discussionmentioning
confidence: 86%
“…Any comparison of these values is virtually prohibited by the existence of two major variables between different laboratories. First, different antisera were used in each laboratory and the characteristics of these are almost certainly different such that the 'gastrin' concentration of the same sample would differ, dependent upon the antisera used (Hansky, Soveny, and Korman, 1974).…”
mentioning
confidence: 99%